Interobserver Variability in Applying American Society of Echocardiography/European Association of Cardiovascular Imaging 2016 Guidelines for Estimation of Left Ventricular Filling Pressure. (January 2019) - Nagueh, Sherif F.; Abraham, Theodore P.; Aurigemma, Gerard P.; Bax, Jeroen J.; Beladan, Carmen; Browning, Alyssa; Chamsi-Pasha, Mohammed A.; Delgado, Victoria; Derumeaux, Genevieve; Dolci, Giulia; Donal, Erwan; Edvardsen, Thor; et al.
Abstract : Background: Assessment of left ventricular (LV) filling pressure is among the important components of a comprehensive echocardiographic report. Previous studies noted wide limits of agreement using 2009 American Society of Echocardiography/European Association of Echocardiography guidelines, but reproducibility of 2016 guidelines update in estimating LV filling pressure is unknown. Methods: Echocardiographic and hemodynamic data were obtained from 50 patients undergoing cardiac catheterization for clinical indications. Clinical and echocardiographic findings but not invasive hemodynamics were provided to 4 groups of observers, including experienced echocardiographers and cardiology fellows. Invasively acquired LV filling pressure was the gold standard. Results: In group I of 8 experienced echocardiographers from the guidelines writing committee, sensitivity for elevated LV filling pressure was 92% for all observers, and specificity was 93±6%. Fleiss κ-value for the agreement in group I was 0.80. In group II of 4 fellows in training, sensitivity was 91±2%, and specificity was 95±2%. Fleiss κ-value for the agreement in group II was 0.94. In group III of 9 experienced echocardiographers who had not participated in drafting the guidelines, sensitivity was 88±5%, and specificity was 91±7%. Fleiss κ-value for the agreement in group III was 0.76. In group IV of 7 other fellows, sensitivity was 91±3%, and specificity was 92±5%. Fleiss κ-value for the agreement in group IV was 0.89. Conclusions: There is a good level of agreement and accuracy in the estimation of LV filling pressure using the American Society of Echocardiography/European Association of Cardiovascular Imaging 2016 recommendations update, irrespective of the experience level of the observer. Abstract : Supplemental Digital Content is available in the text.